Bilateral Radioscopically Guided Erector Spinae Plane Block for Postoperative Analgesia in Spine Surgery: A Randomized Clinical Trial - Beltrame, Sofia Angeles; Fasano, Francisco; Jalón, Pablo (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2022)
Background We compare two perioperative pain management procedures(a radioscopicallyguided erector spinae plane [ESP] block versus the standard wound infiltration technique with local anesthetics) in patients undergoing lumbosacral spine surgery.Methods A randomized, double-blind clinical trial was performed, in which adults at our hospital undergoing lumbosacral surgery without fixation were randomly assigned to receive either the standard wound infiltration technique, employing long-term anesthetics, or a radioscopicallyguided ESP block. Postoperative pain severity, morphine consumption, number of patients immobilized due to wound pain, length of hospitalization, and complications were recorded.Results Over the first 7 postoperative hours, pain relief was superior in the ESP block group among patients who underwent diskectomies or one-level decompression (p< 0.0001). Using an ESP block also was statistically superior at decreasing all postoperative variables recorded in patients scheduled for multilevel decompression: visual analog scale (VAS) pain severity over the first 7 hours after the procedure (p = 0.0004); number of patients with wound pain 1 (p = 0.049), 7 (p< 0.0001), and 24 hours (p = 0.007) after surgery; length of hospitalization (p = 0.0007), number of patients immobilized for wound pain (p = 0.0004) and rescue morphine consumption (p< 0.0001).Conclusion The ESP block is a safe procedure that seems to outperform the infiltration wound technique for postoperative pain management in patients undergoing open spinal surgery. Future studies are needed to verify its effectiveness for arthrodesis/fixation and minimallyinvasive procedures, and for chronic spine pain relief.
Keywords: erector muscles; spinal surgery; postoperative analgesia; nerve block